Pendekatan Model Pembelajaran Flipped Classroom Dengan Media Video Interaktif Untuk Meningkatkan Hasil Belajar Siswa Pada Materi Stoikiometri Di SMA Negeri 3 Manado - Marcho Mangi Antara (Chemistry Department, Universitas Negeri Manado, 2023)
The purpose of this study was to improve student learning outcomes on stoichiometric material by using the flipped classroom learning model with interactive video media at SMA Negeri 3 Manado. This research is a quantitative research using a quasi-experimental design, a study that uses two groups, there is an experimental group and a control group to determine the significant difference between the two groups after treatment. Prior to the treatment, the students were given a pretest (pretest) and after the treatment, the students were given a final test (posttest). The population in this study were all class X IPA SMA Negeri 3 Manado and the sample consisted of 2 classes, namely class X IPA 1 as the experimental class and class X IPA 5 as the control class, each totaling 27 people. The data collection technique used in this research is using tests, tests in this case pretest and posttest. Based on the research data, the results of the t-test analysis at the real level (Î±) = 0.05 were obtained: tcount = 4.87 and ttable = 2.0066, with the experimental class N-Gain test of 0.65 and the control class 0.36. So it can be concluded that there are differences in student learning outcomes using the flipped classroom learning model with interactive video media on stoichiometric material at SMA Negeri 3 Manado.